RECEIVER SYNCHRONIZATION FOR DAB WITH TRANSMISSION MODE III (International Journal of Engineering and Computer Science, 2014)
Synchronization is the key part of OFDM receiver. A method to estimate Time Synchronization in DAB receiver is based on analysis of phase reference symbol is given. Synchronization analysis is performed under Rician channel with SNR 20dB and -8dB.